Uptake of Malaria Vaccine (RTS, S/AS01), Insecticide Treated Nets (ITNs) and Malaria Infections among Children Aged 6-36 Months in Muhoroni Sub-County, Kisumu County Kenya - Okanda, Irine Adhiambo (JOOUST, 2024)
Globally in 2020, about 241 million malaria cases were reported resulting in about 627,000 deaths (Sarfo et al., 2023). Of all the death cases, 96% were from Africa, and 77% of them were children below five years of age (Ng’ang’a et al., 2021)(F. Achieng et al., 2020). Of an estimated 405,000 malaria deaths per year, more than half occur in children below five years and are caused by P. falciparum (Ashley & Poespoprodjo, 2020). Malaria vaccine and Insecticide-treated are among the malaria prevention and control interventions; however, there are limited data on their coverage and their association with the malaria infection. This study aimed to assess the uptake of malaria vaccine and Insecticide-treated nets use and their association with malaria infection among children aged 6-36 months in Muhoroni sub-county, Kisumu county. A cross- sectional study using a quantitative approach was used. The strata and simple random sampling were applied to get 319 children from a 13,502 sample population, and a structured questionnaire was used. Descriptive statistics and Logistic regression were used to describe and determine the association between independent variables and malaria infection using STATA Version 16. The results showed that 67.57% of the children were positive for malaria infection in the past six months. In addition, uptake of RTS, S malaria vaccine is as follows; first dose 72.10% coverage, second dose 66.68%, third dose 59.40%, and fourth dose 31.35%, respectively. Children who did not receive the recommended RTS, S as per their ages were 4 times more likely to get malaria infection than their counterparts who received RTS, S as recommended [AOR=4.07, 95%CI=1.51-11.01, P=0.006]. A child who did not sleep under an insecticide-treated net was 12 times more likely to get malaria infection than a child who slept under an ITN [AOR=11.61,95%CI=1.10-122.59, P=0.041]. With every increase in Age, a child was twice as likely to get malaria infection [ AOR=2.22,95%CI=1.22-4.02, P=0.009]. The study concluded that there is low uptake of RTS, S, especially the third and fourth dose in the Muhoroni sub-county since not a single dose met the World Health Organization uptake target of 90% coverage of each dose, ITN use in the area is high. Not receiving the recommended RTS, S dose and not sleeping under ITN increases the risk of malaria infection. Age was a risk factor for malaria infection. The Study recommended health education initiatives to promote vaccine awareness and targeted interventions to boost malaria vaccine coverage in the region, we recommended the need for further studies to find reasons for low malaria vaccine uptake.
Keywords: Malaria Vaccine (RTS, S/AS01); Insecticide Treated Nets (ITNs); Malaria; Children Aged 6-36 Months